IMPROVING ENGLISH COMMUNICATION SKILLS OF ENGINEERING STUDENTS THROUGH PROJECT-BASED LEARNING (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article discusses the implementation of Project-Based Learning (PBL) as a strategy to improve English communication skills among engineering students. The paper highlights the importance of communication in technical fields and explores how PBL provides a dynamic, practical approach to developing language proficiency. Through team-based tasks, presentations, and real-life simulations, students acquire functional vocabulary, interpersonal communication, and public speaking skills. The study also addresses challenges in applying PBL in technical contexts and suggests recommendations for successful integration. The conclusion emphasizes PBL as a holistic method that aligns language learning with engineering education goals.